Frequency of Physical Restraint and Its Associations With Demographic and Clinical Characteristics in a Chinese Psychiatric Institution. Issue 4 (20th November 2013) - Zhu, Xiao‐Min; Xiang, Yu‐Tao; Zhou, Jian‐Song; Gou, Lei; Himelhoch, Seth; Ungvari, Gabor S.; Chiu, Helen F. K.; Lai, Kelly Y. C.; Wang, Xiao‐Ping
<x xml:space="preserve">Abstract</x> Purpose Physical restraint (PR) is a highly controversal topic in psychiatry. Little is known about PR among psychiatric inpatients in China. This study examined the frequency of PR and its relationships with demographic and clinical characteristics among a large psychiatric institution in the Hunan Province, China. Design and Methods The study included a consecutively assessed sample of 160 psychiatric inpatients. Sociodemographic and clinical data including use of PR were collected from the medical records using a form designed for this study and confirmed via interview. Findings The frequency of PR was 51.3% in the whole sample; 63.2% among female and 39.2% among male patients. In multiple logistic regression analysis PR was independently associated with male gender (p = 0.001, odds ratio [OR] = 0.2, 95% confidence interval [CI] 0.1–0.6), less outpatient treatment prior to admission (p = 0.03, OR = 0.3, 95% CI 0.1–0.9), more frequent use of mood stabilizers (p = 0.002, OR = 5.6, 95% CI 1.9–16.7), more aggressive behavior prior to admission (p = 0.002, OR = 1.1, 95% CI 1.04–1.2), and younger age (p = 0.04, OR = 0.97, 95% CI 0.93–0.99). Practice Implications PR is very common in clinical practice in China. Its demographic and clinical correlates are similar to findings in Western settings.